OPTOELECTRONIC PROPERTIES OF CdS – AgInS2 SOLAR CELLS - M. A. Abdullaev; D. A. Alkhasova (Юг России: экология, развитие, 2016)
Aim. To conduct experimental studies of optoelectronic properties of CdS - AgInS2 solar cells.Methods. AgInS2 films for solar cell CdS-AgInS2 were obtained by magnetron sputtering of crystalline targets derived from bulk ingots. Cadmium sulfide layers were deposited on the AgInS2 films by an electrochemical method in cadmium salts solution, thiourea and ammonia. AgInS2 bulk crystals were obtained in two stages: a direct fusion of the primary components (99,999) in a stoichiometric ratio, followed by directional solidification in a vertical furnace; re-synthesis has been performed on a staggered basis by heating the obtained ingots at temperatures close to the melting points of elements in the two-zone horizontal furnace.Findings. The paper presents the results of experimental studies of the electrical properties and photosensitivity of CdS-AgInS2 film heterojunction obtained by the magnetron. We measured the current-voltage characteristics and quantum efficiency of photoconversion at temperatures up to 250-356 K. We also identified the short circuit current of up to 25 mA/cm2 and open circuit voltage of 0.38 V.Conclusions. The study of the properties of solar cells in recent years has an important place. The results presented in the work would contribute to more efficient conversion of solar energy into electricity.